Papr Reduction In Ofdm System By Using Clipping And Filtering And Weighted Method (International Journal of Engineering and Computer Science, 2015)
In this paper, a peak-to-average-ratio (PAPR) reduction scheme supported a weighted orthogonal frequency-division multiplexing (OFDM) signal is projected to cut back the PAPR while not distortion in removing the burden at the receiver aspect. within the projected theme, a weight is obligatory on every separate OFDM signal via a definite reasonably a band limited signal, associate degreed an OFDM signal fashioned with the weighted separate data is then thought of before a high power electronic equipment (HPA), whereas the original signal are often recovered fully at the receiver aspect. Meanwhile, the time period required to transmit the weighted OFDM signal is that the same because the time period for the first OFDM signal. The performance of the proposed scheme is estimated with Mat lab Simulator. With respect to the theoretical analysis, the weighted OFDM signal PAPR is smaller than that of the clipping and filtering (C&F) methodology, and also the bit-error-rate (BER) performance of the weighted OFDM system is improved compared with the C&F methodology. Here, the projected methodology is easier than the C&F method.